Symposium 2: Testing Tasting: Methods assemblages in an online exam - Wright, Steve (Proceedings of the International Conference on Networked Learning, 2014)
This paper explores the historical contingencies and networks of relations enacted in the Beer Judge Certification Program (BJCP) online exam, designed “to test a prospective judge’s knowledge of beer styles, beer characteristics and the brewing process”. Drawing on the work of John Law the exam is considered as a methods assemblage crafting presences, manifest absences and othered realities. Using accounts from auto-ethnographic recordings and ethnographic fieldwork together with documents, I trace associations from the exam questions and the way they use language to compare beer styles and descriptions. I consider the historical development of these methods of description through the work of Shapin (2012) who explores how these are connected to historic shifts in the way taste, and the tasting body, was understood in the late 18th to early 19th centuries and the orphaning of taste from scientific practice. I then examine how this shift opened changes from a sparse to ornate vocabulary to described the tasted object and the ways that this vocabulary has developed both in connection and in contrast the language of wine. I turn to consider efforts to create devices that standardise this vocabulary and their use for purposes of beer judging in the BJCP. I ask whether the ways that bodies, objects and devices are described and related can be considered to assemble a "community of amateurs" as suggested by Hennion (2004, 2007). I suggest that the reflexive accounts of the participant organisation in describing this as a "program" are more appropriate than the term community. I conclude by considering what contribution an engagement with the concept of a methods assemblage can make to the discussions around tasting and the BJCP, and the broader potentials for networked learning research.